Antenna morphology and sensilla microstructure of the male and female scarab beetle, Lepidiota mansueta Burmeister (Coleoptera: Scarabaeidae). Issue 3 (3rd July 2017) - Handique, Gautam; Bhattacharyya, Badal; Baruah, Abu Adil Lutful Haque; Boruah, Ratan
Abstract: Studies on Lepidiota mansueta Burmeister were conducted to describe and compare the external morphology of the antenna and its sensilla of male and females. Distinct variations were observed in antennal segments between the sexes with males possessing longer scape, pedicel, flagellum and lamellar club segments. Variation was also seen in the antennal sensilla, with males possessing three different types of sensilla while the females possessed seven types of sensilla. Sensilla trichodea (TRS), sensilla placodea (PLAS) type I and sensilla placodea (PLAS) type II were common in both sexes while sensilla chaetica (CHS), sensilla auricilica (AUS) type I, sensilla auricilica (AUS) type II and sensilla auricilica (AUS) type III were found only in females.